Core based trees (CBT). - Ballardie, Tony (Computer communication review.)
One of the central problems in one-to-many wide-area communications is forming the delivery tree - the collection of nodes and links that a multicast packet traverses. Significant problems remain to be solved in the area of multicast tree formation, the problem of scaling being paramount among these.In this paper we show how the current IP multicast architecture scales poorly (by scale poorly, we mean consume too much memory, bandwidth, or too many processing resources), and subsequently present a multicast protocol based on a new scalable architecture that is low-cost, relatively simple, and efficient. We also show how this architecture is decoupled from (though dependent on) unicast routing, and is therefore easy to install in an internet that comprises multiple heterogeneous unicast routing algorithms.